OPTIMUM CONDITION OF BIOETANOL PRODUCTION VIA ACIDIC HYDROLYSIS FROM PINEAPLE (Ananas comosus Merr.) PEEL WASTE IN KUALU VILLAGE-KAMPAR - Hilma, Rahmiwati; Akbar, Unggul; Prasetya, - (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2017)
Bioethanol is an alternative and potential fuel derived from plants, which has the ability to reduce CO2 emissions. It contains sugar that can be utilized and processed into bioethanol. This study aims to produce bioethanol from pineapple peel (Ananas comosus Merr.) through acidic hydrolysis and fermentation process using Sacharomyces cereviceae. This research was expected to know the optimum condition of S. Cereviceae mass and the time of fermentation on the conversion of pineapple peel into bioethanol towards amount and content of ethanol produced. The hydrolysis was using sulfuric acid (H2SO4), fermented with variations yeast 20, 40 and 60 gram and 2, 4 and 6 days of time variations. The resulting bioethanol was purified using a distillation process, then analyzed by gas chromatography. The results showed that optimum ethanol content was obtain in yeasts 20 and 40 grams and 2 days of fermentation. The resulting ethanol content was 26.3% and 24.6%.